A Note on Cryptocarya caesia Bl. (Lauraceae) from Andaman Islands - Mathew, Sam P. (Indian Forester, 1995)
The present paper accounts Jor the re-discovery of Cryptocarya caesia BI. After 73 years from Mt. Harriet hill ranges, South Andamans.